Digitalizing makhārij al-ḥurūf: Leveraging Praat for English Pronunciation Improvement in Islamic Education - Maskur; Azizah; Fithriyah (Journal of Innovation in English Education and Language Teaching, 2024)
This research investigates the integration of Praat technology with makhārij al-ḥurūf to enhance English pronunciation skills among students of Islamic education. The primary objective is to assist students in differentiating between long and short vowels in English through acoustic analysis using Praat, with a particular focus on duration and formant visualization. By addressing nuanced phonemic distinctions, such as the contrasts between "sheep" and "ship," the study also explores students' perceptions and challenges associated with adopting digital pronunciation techniques, including the application of Praat and digitalized makhārij al-ḥurūf. The study employed a quasi-experimental design in which one group was taught via traditional methods (control group) and the other experimental group was taught using methods that integrated Praat into instruction (experimental group). Statistical analysis indicated substantial differences between the two groups, the experimental one showed similar trends for increased scores in accuracy (80%), fluency (85%), and clarity (75%); all higher than the control group. The Likert-scale survey further indicated that experimental students perceived greater comfort and motivation when learning pronunciation with technological means. The proposed Digital-Articulatory Alignment (DAA) theory is a sequel to the traditional articulatory knowledge of Makhārij al ḥurūf but conveyed through the modern understanding of acoustic toolkits such as that of Praat. Through this novel framework, we bridged traditional practices with technology to deliver pronunciation instruction in a more engaging and impactful manner. Specifically, the results cannot be generalised to non-Islamic educational or cultural environments. Future research might adapt this method to wider locations, investigate the creation of AI-based solutions that combine articulatory and acoustic analysis, and study the residual effects on pronunciation abilities and motivation for learning. This is a new perspective on combining the traditional pronunciation teaching context in Islamic education with technology